Guest Editorial: Special Section on Protection and Control of Smart Grid with High Penetration of Converter Interfaced Generation Resources - Juan M. Gers (IEEE, 2021)
Electrical system characteristics are changing substantially as the penetration levels of renewable generation and in general converter interfaced generation resources (CIGRs) increase. The operation of these systems constitutes a challenge for the engineering in protection and control systems.